Development of a PLC-based 4-level lift simulator as a learning medium for electric motor installation - Daniel Maringga; Wanapri Pangaribuan; Jonner Manihuruk; Darni Paranita (Indonesian Journal of Educational Development (IJED), 2026)
The development of industrial automation requires learning media that are relevant to the needs of the world of work, particularly for mastering Programmable Logic Controllers (PLCs) in vocational education. This study aims to develop a four-storey lift simulator based on Omron CP1E PLC as a learning medium for the Electric Motor Installation subject in class XII TITL at SMK Negeri 5 Medan. The research method used the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research population consisted of 31 students using a total sampling technique. Data were obtained from questionnaires validated by media and subject-matter experts, as well as from student responses. The results showed that the media received a feasibility score of 89.3% from media experts and 92.5% from subject matter experts, categorised as highly feasible, and a student response score of 88.3%, categorised as very good. These findings indicate that PLC-based lift simulators are effective in improving students' understanding, motivation, and practical skills in industrial automation systems. The study recommends further development by integrating IoT or HMI to more closely resemble real industrial systems.